Impactos do manejo do solo em área de pastagem extensiva convertida em cultivo de cana-de-açúcar e em pastagem intensiva - Bento, Camila Bolfarini (2020)
Future decreases in greenhouse gas emissions due the use of ethanol have been associated with the way in which changes in land use will occur for new sugarcane crops. One of the main consequences of the increases in the sugarcane planted areas is the expansion toward pasture land. Depending on the management system adopted during the conversion from pasture to sugarcane, the soil structure and greenhouse gas emissions may be negatively altered. In this sense, this project evaluated changes in the levels of potentially toxic metals, the impacts of conversion on the quantity and quality of carbon and on emissions of CO2, CH4 and N2O over six years (2013 to 2019). The experiment was installed on a farm in the municipality of Salto de Pirapora in the State of São Paulo, Brazil. We chose two scenarios in which extensive pasture was the initial condition. In the first, intensification of extensive pasture was carried out. In the second, extensive pasture was converted to sugarcane. Two management activities conventionally carried out in agricultural cultivation areas were adopted, soil preparation and inorganic fertilization. The soil preparation consisted of plowing, harrowing, leveling and opening the sugarcane planting furrows. In the first year, sugarcane was fertilized with 60, 140 and 120 kg ha-1 of NPK. In the sugarcane ratoon years, the fertilizer application rates were 120, 30 and 120 kg ha-1 of NPK. The treatments with intensive pasture had the same rates of fertilizers applied (60, 40 and 40 kg ha-1 of NPK) from 2013 to 2019. Although several of the elements analyzed have increased in comparison to the initial concentration, only the levels of Cd showed increases due to inorganic fertilization. Such increase was in order of 9.54 mg ha-1 year-1. Considering the conversion year (2013) and the last year of evaluations (2019), carbon stocks increased in pasture and sugarcane. The application of fertilizers resulted in a carbon accumulation 30.52% higher in PI than in CA. From 2014 to 2019, the carbon quantified as labile increased by 1% in PE and CA and decrease by 4% in PI. The accumulated CO2 and N2O emissions were higher in fertilized treatments. Pasture treatments were a CH4 source and sugarcane treatments as a CH4 sink to the atmosphere. The CO2-equivalent was 653.7 kg CO2-eq ha-1 higher in PI than in CA. The emission factors were within the range observed by other authors, but below the determined by the IPCC.